Diagnosis of IgG4-Related Tubulointerstitial Nephritis - Raissian, Yassaman (American Society of Nephrology, 2011)
IgG4-related systemic disease is an autoimmune disease that was first recognized in the pancreas but also affects other organs. This disease may manifest as tubulointerstitial nephritis (IgG4-TIN), but its clinicopathologic features in the kidney are not well described. Of the 35 patients with IgG4-TIN whose renal tissue specimens we examined, 27 (77%) had acute or progressive chronic renal failure, 29 (83%) had involvement of other organ systems, and 18 of 23 (78%) had radiographic abnormalities. Elevated total IgG or IgG4 serum levels were present in 79%. All pathologic specimens featured plasma cell–rich TIN, with most showing diffuse, expansile interstitial fibrosis. Immune complexes along the tubular basement membranes were present in 25 of 30 (83%). All specimens had a moderate to marked increase in IgG4+ plasma cells by immunohistochemistry. We used a control group of 175 pathologic specimens with plasma cell–rich interstitial infiltrates that can mimic IgG4-TIN to examine the diagnostic utility of IgG4 immunostaining. Excluding pauci-immune necrotizing and crescentic glomerulonephritis, IgG4 immunohistochemistry had a sensitivity of 100% (95% CI 90–100%) and a specificity of 92% (95% CI 86–95%) for IgG4-TIN. Of the 19 patients with renal failure for whom treatment and follow-up data were available, 17 (89%) responded to prednisone. In summary, because no single test definitively diagnoses IgG4-related systemic disease, we rely on a combination of histologic, immunophenotypic, clinical, radiographic, and laboratory features. When the disease manifests in the kidney, our data support diagnostic criteria that can distinguish IgG4-TIN from other types of TIN.